surveyjoin: a standardized database of scientific trawl surveys in the Northeast Pacific Ocean - Ward, Eric J.; English, Philina A.; Rooper, Christopher N.; Ferriss, Bridget E.; Whitmire, Curt E.; Wetzel, Chantel R.; Barnett, Lewis A. K.; Anderson, Sean C.; Thorson, James T.; Johnson, Kelli F.; Indivero, Julia; Markowitz, Emily H. (PeerJ, 2025)
Fisheries management faces challenges due to political, spatial, and ecological complexities, which are further exacerbated by variation or shifts in species distributions. Effective management depends on the ability to integrate fisheries data across political and geographic boundaries. However, such efforts may be hindered by inconsistent data formats, limited data sharing, methodological differences in sampling, and regional governance differences. To address these issues, we introduce the surveyjoin R package, which combines and provides public access to bottom trawl survey data collected in the Northeast Pacific Ocean by NOAA Fisheries and Fisheries and Oceans Canada. This initial database integrates over 3.3 million observations from 14 bottom trawl surveys spanning Alaska, British Columbia, Washington, Oregon, and California from the 1980s to present. This database standardizes variables such as catch-per-unit-effort (CPUE), haul data, and in-situ measurements of bottom temperature. We demonstrate the utility of this database through three case studies. Our first case study develops a coastwide biomass index for Pacific hake (Merluccius productus) using geostatistical index standardization, comparing results to independent acoustic survey estimates. The second case study examines spatial patterns in groundfish community structure, highlighting breakpoints between assemblages in their mixture of life histories and trophic compositions. Our third example applies spatially varying coefficient models to assess sablefish (Anoplopoma fimbria) biomass trends, identifying regional variability in increases in occurrence and biomass. Together, these case studies demonstrate how the surveyjoin R package and database may improve species and ecosystem assessments by providing insights into population trends across geopolitical boundaries. This database and package represent an important step toward offering a scalable framework that can be extended to include additional data types, surveys, and species. By fostering collaboration, transparency, and data-driven decision making, surveyjoin supports international efforts to sustainably manage shared marine resources under dynamic environmental conditions.
Keywords: Groundfish; Trawl surveys; Northeast Pacific Ocean; Fisheries management; Spatial modeling; Species distribution models